The spider genus Kukulcania in South America (Araneae: Filistatidae): a redescription of K. brevipes (Keyserling) and new records of K. hibernalis (Hentz) - Brescovit, Antonio D.; Santos, Adalberto J. (Zootaxa, 2013)
Two species of the spider genus Kukulcania are known from South America. Kukulcania brevipes (Keyserling), originally described from Peru, is here diagnosed, illustrated and redescribed, with several new records provided for eastern Peru and northern Chile. The synanthropic Kukulcania hibernalis (Hentz) is illustrated and diagnosed, with several new records extending the distribution of this species from northern Venezuela to southern Brazil.